POLITENESS STRATEGY IN REQUEST USED IN MANDAILING WEDDING CEREMONY - Hilman Sujaah Siregar; Citra Anggia Putri (TRANSFORM : Journal of English Language Teaching and Learning, 2020)
This study aimed at analyzing the kind politeness strategy in request which represented in Mangalehen Hata Sipaingot of Mandailing Wedding Ceremony. The descriptive qualitative method used to gain the findings of the data itself. From that findings, 11 requests from 6 speakers has been analyzed. And from those, 21 requests filtered throught transcribing the event. Of all 21 requests, it was found that there were 2 politeness strategies used, they were Bald-On record 6 (28,6%), and Positive Politeness 15 (71,4%). Later on, the positive politeness was the dominant type of politeness since the wedding was a sacred ceremony, the using of positive politeness would be found in many ways. The instrument of this study was recording the event and transcribing them into list. And from that list, the categorization would be easy to exctract the data. Thus the writer found that positive politeness that used also similar to another local tribe wedding ceremony